Synchronous HPV-Related Cancer of Bilateral Tonsils Detected Using Transoral Endoscopic Examination with Narrow-Band Imaging - Fukuko Shimizu; Kenji Okami; Koji Ebisumoto; Daisuke Maki; Akihiro Sakai; Go Ogura; Naoya Nakamura; Masahiro Iida (Case Reports in Otolaryngology)
Background. The incidence of human papillomavirus- (HPV-) related oropharyngeal squamous cell carcinoma (OPSCC) has been rapidly increasing worldwide. HPV is reported in approximately 50% cases of OPSCC in Japan. However, there are few reports of synchronous bilateral HPV-positive tonsillar carcinoma, and, in almost all those cases, carcinoma was detected using positron emission tomography/computed tomography and/or bilateral tonsillectomy. Methods and Results. We report the case of a 63-year-old male with bilateral tonsillar carcinoma detected using transoral endoscopic examination with narrow-band imaging (NBI). A biopsy of the bilateral tonsils revealed squamous cell carcinoma, which was demonstrated to be HPV-related using in situ hybridization and p16 immunohistochemistry. The patient was diagnosed as synchronous bilateral tonsillar carcinoma: T1 (2) N2b M0. He was treated with induction chemotherapy, bilateral radical tonsillectomy with neck dissection, and radiotherapy. Conclusion. To our knowledge, this is the first report of a synchronous bilateral tonsillar carcinoma detected using transoral NBI in the outpatient setting. Early diagnosis without the inspection under general anesthesia is beneficial for the patients with lymph node metastasis from unknown primary lesion.